The Importance of Establishing Functional Position of Corporate Supervisor at the Ministry of Law and Human Rights - Jamilus Jamilus (Jurnal Penelitian Hukum De Jure, 2021)
The establishment of Functional Position of Corporate Supervisor is one of the priority working programs to be realized at the Directorate General of Legal Administrative Affairs. This is important, not only to implement the government programs, namely simplifying the bureaucracy, but also to optimize the performance of the Ministry of Law and Human Rights. The question is why it is important to establish the Functional Position of Corporate Supervisor at the Ministry of Law and Human Rights. The research method used is normative and empirical legal research with descriptive research characteristics and a qualitative analysis approach. The results showed that the importance of the Functional Position of Corporate Supervisor at the Ministry of Law and Human Rights is based on the mandate of Presidential Regulation Number 13 Year 2018 and Article 138 to Article 141 of Law Number 40 Year 2007, as well as changes in the institutional structure of the Directorate of Civil Affairs. In order for the mandate of Presidential Regulation Number 13 Year 2018 and Article 138 to Article 141 of Law Number 40 Year 2007 to be realized, the Ministry of Law and Human Rights needs to immediately establish the Functional Position of Corporate Supervisor, and also immediately change the organizational structure of the Directorate of Civil Affairs.